Außenaufnahme
"8. Dr. Eppler, Dr. Baumann, Consul General, Consulate of the Federal Republic of Germany, Ambassador Guenter Diehl and Ambassador Puri, with the Vice President and Secretary of the Mandir at the tablet of the Nandini Precision Works unveiles ba Mr.Partsch in Jan. 1973."; Bemerkungen: in Album geklebt